Optimized OPA1 Isoforms 1 and 7 Provide Therapeutic Benefit in Models of Mitochondrial Dysfunction - Maloney, Daniel M.; Chadderton, Naomi; Millington-Ward, Sophia; Palfi, Arpad; Shortall, Ciara; O’Byrne, James J.; Cassidy, Lorraine; Keegan, David; Humphries, Peter; Kenna, Paul; Farrar, Gwyneth Jane (Frontiers in Neuroscience, 2020)
Optic Atrophy 1 (OPA1) is a mitochondrially targeted GTPase that plays a pivotal role in mitochondrial health, with mutations causing severe mitochondrial dysfunction and typically associated with Dominant Optic Atrophy (DOA), a progressive blinding disease involving retinal ganglion cell loss and optic nerve damage. In the current study, we investigate the use of codon-optimized versions of OPA1 isoform 1 and 7 as potential therapeutic interventions in a range of in vitro and in vivo models of mitochondrial dysfunction. We demonstrate that both isoforms perform equally well in ameliorating mitochondrial dysfunction in OPA1 knockout mouse embryonic fibroblast cells but that OPA1 expression levels require tight regulation for optimal benefit. Of note, we demonstrate for the first time that both OPA1 isoform 1 and 7 can be used independently to protect spatial visual function in a murine model of retinal ganglion cell degeneration caused by mitochondrial dysfunction, as well as providing benefit to mitochondrial bioenergetics in DOA patient derived fibroblast cells. These results highlight the potential value of OPA1-based gene therapy interventions.